A techno-economic assessment on the adoption of latent heat thermal energy storage systems for district cooling optimal dispatch & operations. (1st May 2021) - Mazzoni, Stefano; Sze, Jia Yin; Nastasi, Benedetto; Ooi, Sean; Desideri, Umberto; Romagnoli, Alessandro
Highlights: Phase Change Materials as cold energy storage media to replace ice and water. Thermal energy storage adequate technology for district cooling arrangements. Master-planning and economic dispatch optimized on energy, cost and emissions. District cooling equipped with phase change material storage technology. Mixed Integer Quadratic Programming for master-planning and economic dispatch. Abstract: The adoption of high-density phase change materials as cold thermal energy storage media have been considered as potential alternatives to water and ice. In this paper, the implementation of these media has been investigated in the context of district cooling in mixed-used building micro-grids whereby the cold thermal energy storage is retrofitted into an existing eco-building cluster. The techno-economic feasibility of implementing phase change materials, which includes eutectic salt, polyethylene glycol and paraffin as cold thermal energy storage media for district cooling, have been evaluated by computing the economic dispatch of a cooling bus network using mixed-integer quadratic programming. Furthermore, the impact of high-density storage media with a reduced footprint on the integration and design of cold thermal energy storage systems in district cooling has been included in the analysis. The capital expenditure of cold thermal energy storage systems, the land rental price for required occupancy and operating expenditure are used to determine the net present value after 20 years. Through peak shaving, optimally sized cold thermal energy storage has shown a better alternative substituting one of the two chillers. The smaller chiller (1200 kWc) is no longer required in the plant, giving significant savings in capital expenditure. The cost-benefit analysis also showed that only eutectic salt phase change materials are competitive with ice, with a net present value approaching 200, 000 after 20 years. When phase change materials are adopted, especially if compared with water, the building operations and related costs are significantly less affected by large fluctuations in land rental price given its smaller footprint, thus posing significantly lower financial risks.